2023
DOI: 10.3390/curroncol30120765
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Outcomes after Conservative Management for Patients with Localized Penile Cancer

Simone Cilio,
Antonio Tufano,
Gabriele Pezone
et al.

Abstract: Background: Men with localized invasive penile cancer (PC) can be treated with organ-sparing treatments with different functional and aesthetical outcomes. Thus, the aim of this study is to investigate sexual outcomes in patients with PC confined to the glans that underwent wide local excision (WLE) vs. glansectomy with urethral glanduloplasty. Methods: Complete data from 60 patients with PC were analyzed at our institution from 2017 to 2022. Patients were asked for personal habits and clinical features. PC wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Penile cancer and its treatment have a significant impact on sexual wellbeing, both physiologically and psychologically, with more than 40% of patients impacted negatively post-surgery in at least one of these domains ( 56 – 58 ). Organ sparing procedures are often considered to have better outcomes than more radical approaches ( 21 , 48 , 57 ) however, some reports have shown that sexual outcomes after WLE and glansectomy with urethral glanduloplasty still have some reduction in sexual function. Glanduloplasty patients appear to exhibit a worse international index of Erectile Function (IIEF-5) and Changes in Sexual function (CSFQ) scores post-surgery ( 57 ).…”
Section: Review and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Penile cancer and its treatment have a significant impact on sexual wellbeing, both physiologically and psychologically, with more than 40% of patients impacted negatively post-surgery in at least one of these domains ( 56 – 58 ). Organ sparing procedures are often considered to have better outcomes than more radical approaches ( 21 , 48 , 57 ) however, some reports have shown that sexual outcomes after WLE and glansectomy with urethral glanduloplasty still have some reduction in sexual function. Glanduloplasty patients appear to exhibit a worse international index of Erectile Function (IIEF-5) and Changes in Sexual function (CSFQ) scores post-surgery ( 57 ).…”
Section: Review and Discussionmentioning
confidence: 99%
“…It consists of several aspects including, but not limited to, ability to obtain and maintain erection, achievement of orgasm, sexual desire, intercourse satisfaction and overall sexual satisfaction (56). Penile cancer and its treatment have a significant impact on sexual wellbeing, both physiologically and psychologically, with more than 40% of patients impacted negatively post-surgery in at least one of these domains (56)(57)(58). Organ sparing procedures are often considered to have better outcomes than more radical approaches (21, 48, 57) however, some reports have shown that sexual outcomes after WLE and glansectomy with urethral glanduloplasty still have some reduction in sexual function.…”
Section: Sexual Outcomes After Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…At 12 months post-surgery, those who underwent glansectomy (n = 22) exhibited poorer IIEF-5 and CSFQ scores compared to the wide local excision (WLE) group (n = 12). Patients with diabetes who underwent glansectomy exhibited a higher susceptibility to experiencing erectile dysfunction, with more pronounced dysfunction observed in younger patients [29].…”
Section: Post-treatment Sexual Outcomesmentioning
confidence: 99%
“…To date, surgery stands as the primary treatment for PC. However, for precancerous lesions or early-stage malignancies, less invasive approaches, such as topical chemotherapy with imiquimod or 5-fluorouracil (5-FU), laser therapy, or brachytherapy may be considered, Medicina 2024, 60, 414 2 of 8 since radical treatments may exhibit profound negative impact on the patient's sexual function, quality of life (QOL), social interactions, self-image and self-esteem [3].…”
Section: Introductionmentioning
confidence: 99%